Epidemiology, clinical features, and resource utilization associated with respiratory syncytial virus in the community and hospital. Issue 3 (20th February 2020) - Smithgall, Marie; Maykowski, Philip; Zachariah, Philip; Oberhardt, Matthew; Vargas, Celibell Y.; Reed, Carrie; LaRussa, Philip; Saiman, Lisa; Stockwell, Melissa S.
Abstract: Background: The epidemiology, clinical features, and resource utilization of respiratory syncytial virus (RSV) cases in the community and the hospital are not fully characterized. Methods: We identified individuals of all ages with laboratory‐confirmed RSV from two sources, a community cohort undergoing surveillance for acute respiratory infections (ARIs) and hospitalized patients from the same geographic area of New York City between 2013 and 15. The epidemiology, clinical features, and resource utilization (antibiotic/steroid/ribavirin usage, chest X‐rays, respiratory‐support (continuous positive airway pressure [CPAP], mechanical ventilation or extracorporeal membrane oxygenation [ECMO]), and indicators of disease severity (respiratory‐support, and/or ICU admission or death)) were compared among age groups using univariate and bivariate analyses. Results: In the community cohort (1777 people with 1805 ARIs), 66(3.7%) tested RSV‐positive (3.8% of <1‐year‐olds; 3.8% of adults ≥65); 40.9% were medically attended, and 23.1% reported antibiotic usage. Among 40, 461 tests performed on hospital patients, 2.7% were RSV‐positive within ± 2 days of admission (37.3% <1 year old; 17.4% ≥65 years old). Among RSV‐positive hospitalized adults ≥65%, 92.7%, 89.6% and 78.1% received a chest X‐ray, antibiotics and/or steroids respectively, compared with 48.9%, 45.7%, and 48.7% of children <1. Severe illness occurred in 27.0% RSV‐positive hospitalized <1‐year‐olds and 19.8% ≥65‐year‐olds. Conclusions: Respiratory syncytial virus had a demonstrated impact in the community and hospital. Only 40% of RSV community cases were medically attended. In the hospitalized‐cohort, <1‐ and ≥ 65‐year‐olds accounted for the majority of patients and had similar rates of severe illness. In addition, resource utilization was high in older adults, making both young children and older adults important potential RSV vaccine targets.